Renewable Energies for Central Asia Countries: Economic, Environmental and Social Impacts Proceedings of the NATO SFP Workshop on Renewable Energies for Central Asia Countries: Economic, Environmental and Social - Iacomelli, Aldo.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2005)
In the last few years, awareness and worries about the exhaustion of natural resources are increasing, but this fact is still very much discussed about its analytical measurement, and therefore not yet demonstrated. However, what has been demonstrated is that the 6 billion inhabitants of the Earth move every kind of goods and wares around the world at about 8 tons per capita, which means about 50 billion tons per year. This is the same amount as is moved yearly by natural forces, such as winds, eruptions, earthquakes, rain. Since the Kyoto Protocol entered into force on 16 February 2005 an investment on rational use of energy, savings and efficiency is the main premise supporting the development of new energy sources needed to meet the target of the KP and UNFCCC. If energy consumption decreases, renewable sources could cover a significant part of the demand of energy (in particular electricity), if consumption remains uselessly high because inefficient and less energy-consuming (acting also on final uses), renewable energy would become a reality, a feasible method even in these sectors. With investments being equal (today all in the sector of generation from fossil sources), if there were parallel researches on how to reduce consumption and wastes considerably (at least 35%) and on power plants from renewable sources, there would be also a reduction of gas emissions, without any negative influence on development. New technologies (and new "energy products") will play a crucial role in the development of a market of "sustainable energy products" that should grow in a competitive way (cost-effective) to stand against the challenge of change.
Renewable Energy (RE), Energy Efficiency (EE) & Energy Services: The Energy Market Transformation -- Promoting Effective and Efficient Public Private Partnerships (PPPs) -- The Clean Development Mechanism: New Instrument in Financing Renewable Energy Technologies -- International Co-Operation on Energy Technologies Research and Development -- Market Deployment of Renewable Energy in Central Asia: Implications for Energy Diversification -- World Energy Outlook 2004: Key Findings and Messages -- Main Achievements of the IEA Programme on Hydropower Technologies -- Renewable Resources to Hydrogen: Appropriated Technologies for Developing Countries -- The Conception of the Use of Renewable Energy Sources and Their Role in the Energy Balance of Uzbekistan -- Current State and Prospects of Renewable Energy Technology in Russia -- The Hybrid Solar - Wind Source of the Electro Energy and Prospect of Its Application -- New Methods for Improvement of Efficiency of Solar Cells on the Basic Si-Monocrystals -- Design of Semiconductor Nanostructures for Solar Cell Application -- Utilization Possibilities of Renewable Sources of Energy in Southern Kazakhstan by the Example of Karatausko-Ugamski Energy Complex -- Renewable Energy: Environmental and Nature Protection Aspects -- To the Problem of Production and Using of Biofuel in Conditions of Uzbekistan.
Keywords: ENVIRONMENTAL SCIENCES; ENGINEERING ECONOMY; ENVIRONMENTAL MANAGEMENT; ECONOMICS; ENVIRONMENTAL ECONOMICS; ENVIRONMENT; RENEWABLE ENERGY SOURCES; ENERGY ECONOMICS; ENVIRONMENTAL MANAGEMENT; R & D/TECHNOLOGY POLICY; ENVIRONMENTAL ECONOMICS